Problems and techniques of administrative training in Africa - Adedeji, Adebayo; Ahmadu Bello University; Institute of Public Administration (Ghana) (Ile-Ife, Nigeria : University of Ife Press, 1969)
This book was derived from the conference on Administrative Training Techniques held at the Institute of Administration, University of Ife. The book outlined some of the problems which every institute or school of public administration has had to face and resolve.
Includes bibliographical references and index
ahz 08/04/2019
Loans
Keywords: Public administration--Study and teaching; Public administration; Africa